Discussing impact assessment on creative tourism: A theoretical and analytical model - Tomaz, Elisabete (2020)
Over the last decades, tourism has experienced exponential growth, expansion and diversification, being considered one of the most important socio-economic sectors, an essential source of income and employment for many territories (e.g. Bellini et al. 2017; Romão and Nijkamp 2017; Weidenfeld 2018). In response to the concerns about the negative impacts of tourism and to improve the relationship between hosts and tourists, culture-based creativity is seen as a path to create competitive advantages and improve more sustainable practices in the tourism field. Therefore, many cities and regions have sought to reinvent themselves as creative tourist destinations, by encouraging synergies between tourism and the cultural and creative activities to foster the development of new products, experiences and markets (Delisle and Jolin 2007; Duxbury and Richards 2019; Richards and Wilson 2007). Despite the high attractiveness of large capitals and metropolises, small towns and rural areas can also benefit from the growth of tourist flows and the demand for less overcrowded tourist destinations. Alternatively, they can offer interactive, small-scale, unique and tailor-made experiences based on local culture, lifestyles, and values thus generating potential positive impacts on these communities (Richards and Duif 2018; Wisansing and Vongvisitsin 2019). In the discussion of tourism development models, sustainability has become an unavoidable frame of reference, introducing cultural, social and environmental concerns, in addition to the analysis of economic issues. In this vein, we consider the integration of culture as a fundamental dimension of the analysis, together and in interrelation with the economic, social and environmental dimensions. Although the impact assessment exercises have focused on predominantly economic indicators, there is an increasing number of methods that can determine and monitor more accurately the multiple links and impacts of tourist activities in local communities, and also address sustainability issues. This paper has the objective of review the main theoretical and methodological approaches about impact assessment, to develop a comprehensive and operational framework capable of contributing to a better understanding the multifaced nature of creative tourism and their diverse impacts to support the formulation of policies for the sector and according to each context.